Foliar application of titanium on potato crop - Bacilieri, Fernando Simoni; Lana, Regina Maria Quintão; Oliveira, Roberta Camargos; Luz, José Magno Queiroz (Comunicata Scientiae, 2022)
Although titanium (Ti) is not considered a nutrient, researches demonstrate that Ti leaf application can provide beneficial effects on plants growth. The objective of this study was to evaluate the influence of foliar applications of Ti levels on the metabolism, nutrient uptake and yield of potato crop, Agate cultivar. The experiment was conducted in a randomized complete block design with five treatments and four replications. The treatments were composed of 0, 10.2, 15.3, 20.4 and 22.9 g Ti ha-1, divided into three applications during the growth stage, tuberization stage and tuber filling stage. Foliar applications of Ti increase the chlorophyll content (Spad value) in the tuber filling stage. Ti levels do not interfere with N, Zn and Cu nutrient accumulation. Increasing Ti levels linearly reduce the Mn, lipid peroxidation (PL) and urease content and increase the activity of peroxidase (POD), nitrate reductase (ANR), catalase (CAT), proline and Fe content in the growth stage, with maximum level around 3 to 6 g Ti ha-1. In the tuberization stage, at high levels of Ti, there is an increase in urease activity and CAT while ANR has its lowest value. In the tuber filling stage, high Ti levels are related to high Fe, Mn, high ANR and superoxide dismutase (SOD) activity and low PL activity. The ideal level of titanium applied by leaf for greater yield of tubers is 11.3 g of Ti ha-1.